2017
DOI: 10.1155/2017/2432957
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations in Candidate Genes and Intergenic Regions Affect Body Mass Index and Abdominal Obesity in Mexican Children

Abstract: Introduction. Increase in body weight is a gradual process that usually begins in childhood and in adolescence as a result of multiple interactions among environmental and genetic factors. This study aimed to analyze the relationship between copy number variants (CNVs) in five genes and four intergenic regions with obesity in Mexican children. Methods. We studied 1423 children aged 6–12 years. Anthropometric measurements and blood levels of biochemical parameters were obtained. Identification of CNVs was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…As with all association studies, this could be due to an array of factors including ethnic, study design and methodological differences, or gene-environment interactions, among others [ 36 , 37 ]. The lack of association of the 1p31.1/ NEGR1 CNV is in agreement with previous reports in Mexican children and adults where rs2815752 (in high LD with 1p31.1/ NEGR1 CNV) was not associated with obesity [ 12 , 38 ], but in disagreement with the findings of Antúnez-Ortiz et al who found a significant association of another NEGR1 CNV in a group of Mexican children [ 39 ]. Regarding the GPCR5 CNV, it has been previously suggested that the effect of the deletion of CNV is ethnic-specific, as it was significantly associated with obesity in Europeans, who have a higher CNV deletion frequency (0.27); but not in the Chinese population who have a lower CNV deletion frequency (0.008) [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
“…As with all association studies, this could be due to an array of factors including ethnic, study design and methodological differences, or gene-environment interactions, among others [ 36 , 37 ]. The lack of association of the 1p31.1/ NEGR1 CNV is in agreement with previous reports in Mexican children and adults where rs2815752 (in high LD with 1p31.1/ NEGR1 CNV) was not associated with obesity [ 12 , 38 ], but in disagreement with the findings of Antúnez-Ortiz et al who found a significant association of another NEGR1 CNV in a group of Mexican children [ 39 ]. Regarding the GPCR5 CNV, it has been previously suggested that the effect of the deletion of CNV is ethnic-specific, as it was significantly associated with obesity in Europeans, who have a higher CNV deletion frequency (0.27); but not in the Chinese population who have a lower CNV deletion frequency (0.008) [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
“…4 5 The majority of fat is stored in the subcutaneous adipose tissue even though, in some individuals, excessive amounts may be accumulated intra-abdominally (visceral fat). 2 The visceral accumulation of body fat is due to genetic factors, [6][7][8][9][10][11][12] neuroendocrine perturbations 13 and environmental and lifestyle factors. 14 The combination of over consumption of energy-dense food and a sedentary lifestyle are well known to play a role in the accumulation of visceral fat.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, works revealed by Xu et al [ 20 , 21 ], Yang et al [ 26 ] and Liu et al [ 24 ] found that gains in the copy number of the MYH3, MICAL-L1, CYP4A11 and MAPK10 genes were associated with high body weight, chest girth, body length and height in Chinese cattle. In agreement with these findings, losses in copy numbers of the insulin ( INS ) gene were associated with increased body mass index and waist circumference in humans [ 56 ]. Disagreement with these findings, gains in copy numbers of LEPR and neuronal growth regulator 1 ( NEGR1 ) gene were associated with a decreased body mass index, waist circumference and risk of abdominal obesity in human [ 56 ].…”
Section: Discussionmentioning
confidence: 74%
“…In agreement with these findings, losses in copy numbers of the insulin ( INS ) gene were associated with increased body mass index and waist circumference in humans [ 56 ]. Disagreement with these findings, gains in copy numbers of LEPR and neuronal growth regulator 1 ( NEGR1 ) gene were associated with a decreased body mass index, waist circumference and risk of abdominal obesity in human [ 56 ]. Various CNVs unquestionably exert significant effects on meat production and reproduction traits in cattle [ 57 ].…”
Section: Discussionmentioning
confidence: 74%